The construction of identity in Alice Walker's The Color Purple and Zora Neale Hurston's Their Eyes Were Watching God - Nodari, Janice Inês (2002)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.